Housing Condition of Coastal Area in Bangladesh: A Case Study of Kutubdia, Coxs Bazaar (Journal of Environmental Science and Natural Resources, 2015)
This study was conducted to determine the contamination of E. coli and Salmonella for different types of foods in Chittagong city area. In case of laboratory examination, almost half (49.58%) of the samples were contaminated where 28.75% positive for E. coli. and 20.83% for Salmonella. The positive cases for type A sample was 20 out of 96 constituting 20.83% whereas the positive cases for type B sample was 49 out of 144 constituting 34.03% for E. coli. The positive cases of type A sample was 15 out of 96 making up 15.63% and for type B sample was 35 out of 144 making up 24.31% for Salmonella.A chi-square (?2) test was used to examine the equality of observed proportions for E. coli and Salmonella of each item of both types of food where significant difference among the observed proportion for E. coli (p-value